PENINGKATAN PENGETAHUAN PENYUSUNAN SOAL BERBASIS HOTS PADA GURU BAHASA INGGRIS SMAN 1 KOTAGAJAH - Dian Puspita; Berlinda Mandasari; Kamelia Sari (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
One indicator of the success of education is the good quality of teachers. Permendiknas Number 16 of 2007 concerning Academic Qualification Standards and Competency of Subject Teachers states that teachers must have competencies, one of which is the competence to develop assessment instruments, both assessment of learning processes and assessment of learning outcomes. This is very important to measure the learning outcomes that have been set in the curriculum. In fact, English teachers at SMA Negeri 1 Kotagajah were still lacked in compiling exam questions using HOTS criteria. Therefore, the training program to create HOTS based test for English teachers at SMA Negeri 1 Kotagajah was implemented. Based on the results of the pre-test and post-test conducted, it was found that there was an increase in knowledge about the preparation of HOTS-based questions by the English teacher of SMA Negeri 1 Kotagajah.